Acquisition of cancer stem cell‐like properties in non‐small cell lung cancer with acquired resistance to afatinib. Issue 10 (30th September 2015) - Hashida, Shinsuke; Yamamoto, Hiromasa; Shien, Kazuhiko; Miyoshi, Yuichiro; Ohtsuka, Tomoaki; Suzawa, Ken; Watanabe, Mototsugu; Maki, Yuho; Soh, Junichi; Asano, Hiroaki; Tsukuda, Kazunori; Miyoshi, Shinichiro; et al.
Abstract : Afatinib is an irreversible epidermal growth factor receptor (EGFR)‐tyrosine kinase inhibitor (TKI) that is known to be effective against the EGFR T790M variant, which accounts for half of the mechanisms of acquired resistance to reversible EGFR‐TKIs. However, acquired resistance to afatinib was also observed in clinical use. Thus, elucidating and overcoming the mechanisms of resistance are important issues in the treatment of non‐small cell lung cancer. In this study, we established various afatinib‐resistant cell lines and investigated the resistance mechanisms. EGFR T790M mutations were not detected using direct sequencing in established resistant cells. Several afatinib‐resistant cell lines displayed MET amplification, and these cells were sensitive to the combination of afatinib plus crizotinib. As a further investigation, a cell line that acquired resistance to afatinib plus crizotinib, HCC827‐ACR, was established from one of the MET amplified‐cell lines. Several afatinib‐resistant cell lines including HCC827‐ACR displayed epithelial‐to‐mesenchymal transition (EMT) features and epigenetic silencing of miR‐200c, which is a suppresser of EMT. In addition, these cell lines also exhibited overexpression of ALDH1A1 and ABCB1, which are putative stem cell markers, and resistance to docetaxel. In conclusion, we established afatinib‐resistant cells and found that MET amplification, EMT, and stem cell‐like features are observed in cells with acquired resistance to EGFR‐TKIs. This finding may provide clues to overcoming resistance to EGFR‐TKIs. Abstract : We established non‐small cell lung cancer cell lines with acquired resistance to afatinib. It was shown that MET amplification, EMT or stem‐cell like properties were acquired. While resistance with MET amplification was overcame by combination of afatinib plus crizotinib, the combination therapy induced acquisition of resistance related to stem‐cell like properties.